Physical activity level of students of a public school in a city of Rio Grande do Sul - Franciele Dresch; Josefina Bertoli; José Raphael Leandro Costa Silva; Anderson Simas Frutuoso; Cíntia de la Rocha Freitas (Universidade de Fortaleza, 2014)
Objective: To diagnose the level of physical activity of 15-18-year-old students of a public school in a city of the state of Rio Grande do Sul, Southern Brazil. Methods: This is a quantitative cross-sectional study. The short version of the International Physical Activity Questionnaire (IPAQ) was used. The level of physical activity was compared between female and male students using the Mann-Whitney test. Kruskal-Wallis Test was used to compare same-sex individuals at different ages. All the analyses used a significance level of 0.05. Results: It was observed that 57.5% (n = 309) of the students were active, 26.3% (n = 141) moderately active and 16.2% (n = 87) inactive, with a higher level of physical activity among male adolescents. It could be found that 59.6% (n = 136) of the boys and 56% (n = 176) of the girls were classified as vigorously active. Activities such as walking are carried out more frequently (5.36 days / week) if compared with the moderate (3.74 days / week) and vigorous activities (2.06 days / week). Conclusion: There was a higher prevalence of individuals classified as vigorously active followed by moderately active and extremely inactive. Male adolescents are more active than their female peers. doi:10.5020/18061230.2013.p365